The administrative skills of school administrators affecting the Standard Operating Procedures (SOPs) of Internal Quality Assurance (IQA) of schools under the office of Ratchaburi Primary Educational Service Area 2 - Plaikaew, Chanita (Journal of Management Science Nakhon Pathom Rajabhat University, 2020)
This research aimed to: 1) study the level of administrative skills of school administrators; 2) study the level of the Standard Operating Procedures (SOPs) of Internal Quality Assurance (IQA) of schools; and 3) analyze administrative skills of school administrators effecting the Standard Operating Procedures (SOPs) of schools’ Internal Quality Assurance (IQA). The research sample was 302 teachers derived by proportional stratified random sampling as distributed by district. The research instrument was a questionnaire constructed by the researcher with the Content Validity Index (CVI) ranged from 0.67 to 1.00. The internal consistency reliability coefficients of the questionnaire were 0.96 for administrative skills of school administrators 0.98 for effectiveness of the Standard Operating Procedures (SOPs) of Internal Quality Assurance (IQA). Data were analyzed with percentage, mean, standard deviation and stepwise multiple regression. The research results showed that: 1. Overall and in specific aspects, level of the administrative skills was at a high level. These aspects were conceptual skills, evaluative skills, technical skills, leadership skills, educational skills, interpersonal skills, and human resource management skills. 2. Overall and in specific aspects, level of effectiveness of the Standard Operating Procedures (SOPs) of Internal Quality Assurance (IQA) was at a high level. These aspects were quality of learners, administrative and management processes, and teaching and learning management emphasizing on student-centered learning. 3. The administrative skills of school administrators in the aspects of evaluation skills (X7), conceptual skills (X4), leadership skills, educational skills (X6), technical skills (X2) together predicted effectiveness of the Standard Operating Procedures (SOPs) of Internal Quality Assurance (IQA) at the percentage of 66.80 with statistical significance level of .01. The regression equation was Ŷ_tot = 0.82 + 0.38 (X7) + 0.14 (X4) + 0.16 (X6) + 0.15(X2) Article history : Received 21 February 2019 Revised 26 March 2019 Accepted 29 March 2019 SIMILARITY INDEX = 1.00 %